2019
DOI: 10.1177/2167702619863769
|View full text |Cite
|
Sign up to set email alerts
|

Disgust Theory Through the Lens of Psychiatric Medicine

Abstract: The elicitors of disgust are heterogeneous, which makes attributing one function to disgust challenging. Theorists have proposed that disgust solves multiple adaptive problems and comprises multiple functional domains. However, theories conflict with regard to what the domains are and how they should be delineated. In this article, we examine clinical evidence of aberrant disgust symptoms in the contamination subtype of obsessive-compulsive disorder, blood-injury-injection phobia, and posttraumatic stress diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Additional supporting information can be found at http:// journals.sagepub.com/doi/suppl/10.1177/2167702620951510 Note 1. We conducted similar analyses using the complete TDDS, which includes seven-item pathogen, sexual, and moral subscales (for a review of this instrument's clinical utility, see Amoroso et al, 2020). A factor analysis indicated four separate factors (contamination sensitivity and pathogen, sexual, and moral disgust).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional supporting information can be found at http:// journals.sagepub.com/doi/suppl/10.1177/2167702620951510 Note 1. We conducted similar analyses using the complete TDDS, which includes seven-item pathogen, sexual, and moral subscales (for a review of this instrument's clinical utility, see Amoroso et al, 2020). A factor analysis indicated four separate factors (contamination sensitivity and pathogen, sexual, and moral disgust).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Clinical research on disgust proneness has sparked hypotheses regarding the etiology of such disorders with the goal of tailoring interventions to target characteristics of disgust not shared by general anxiety or fear (e.g., its distinct developmental inputs, mechanistic underpinnings, and resistance to extinction; Amoroso et al, 2020; Knowles, Cox, Armstrong, & Olatunji, 2019; Olatunji et al, 2017). One prominent hypothesis suggests that higher disgust proneness leads to an overestimate of the threat posed by infectious disease, which in turn leads to vigilance toward pathogen cues and, consequently, downstream anxiety (Olatunji et al, 2017; Widen & Olatunji, 2016).…”
mentioning
confidence: 99%
“…A rapidly expanding literature has revealed the implications of these aspects of the behavioral immune system for phenomena ranging from political ideology [26,27] to intergroup relations [24,28], to psychopathology [29][30][31]. Even so, the behavioral immune system framework might have more limited application to pandemics than researchers realize.…”
Section: Insights From the Behavioral Immune Systemmentioning
confidence: 99%
“…Disgust may contribute to anxiety which also leads to obsessive disorder and may cause posttraumatic stress syndromes [30] which is likely to lead to maternal health complications. In this study, disgust is shown to be significantly associated with the development of PE-E, with 25.9% reduced odds of developing PE-E compared to those who were not disgusted during pregnancy.…”
Section: Discussionmentioning
confidence: 99%